Fish diversity and water quality during flood mitigation works at Semariang Mangrove Area, Kuching, Sarawak, Malaysia - L, Nyanti; R, Nur ‘Asikin; T.Y, Ling; G, Jongkar (Universiti Kebangsaan Malaysia, 2012)
This study aimed to document the fish diversity and water quality at Semariang mangrove area, Kuching, Sarawak, which is located at the eastern part of Kuching Wetland National Park. Field samplings were carried out in 2009 during the construction of the flood mitigation channel at the eastern part of the park. A total of 21 families represented by 37 species of fish were caught from the area. The six dominant families in terms of the number of individuals caught were Mugilidae (16%), Leiognathidae (16%), Ambassidae (11%), Ariidae (9%), Lutjanidae (8%) and Plotosidae (6%). In terms of the percentage of six dominant genera based on the number of individuals caught, 16% was represented by Valamugil, 11% by Ambassis, 10% by Gazza, 9% by Arius, 8% by Lutjanus and 6% by Plotosus. The values of diversity and richness indices were lower at stations located close to the flood mitigation channel. Similarly, the concentrations of dissolved oxygen were lower and total suspended solids were significantly higher at stations close to the channel and sand mining area. Therefore, fish fauna and water quality at Semariang mangrove area were affected during the construction of the flood mitigation channel.